2018
DOI: 10.1002/mc.22937
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling dynamics in head and neck squamous cell cancer tumor‐stroma interactions

Abstract: Wnt pathway activation maintains the cancer stem cell (CSC) phenotype and promotes tumor progression, making it an attractive target for anti‐cancer therapy. Wnt signaling at the tumor and tumor microenvironment (TME) front have not been investigated in depth in head and neck squamous cell carcinoma (HNSCC). In a cohort of 48 HNSCCs, increased Wnt signaling, including Wnt genes (AXIN2, LGR6, WISP1) and stem cell factors (RET, SOX5, KIT), were associated with a more advanced clinical stage. Key Wnt pathway prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…It has been found that Wnt activation was greatest at the boundary between epithelial and stromal compartments, and both cancer cells and cancer-associated fibroblasts mediated reciprocal stimulation by paracrine signals, mainly WNT-3A. In this model, the activation of canonical Wnt signaling induced stemness and increased invasive potential [66]. Several other studies also documented the relationship between Wnt signaling and cell invasion.…”
Section: Functional Significance Of Wnt/β-catenin Pathway Dysregulationmentioning
confidence: 61%
See 1 more Smart Citation
“…It has been found that Wnt activation was greatest at the boundary between epithelial and stromal compartments, and both cancer cells and cancer-associated fibroblasts mediated reciprocal stimulation by paracrine signals, mainly WNT-3A. In this model, the activation of canonical Wnt signaling induced stemness and increased invasive potential [66]. Several other studies also documented the relationship between Wnt signaling and cell invasion.…”
Section: Functional Significance Of Wnt/β-catenin Pathway Dysregulationmentioning
confidence: 61%
“…Another study found that a quarter of OSCC showed overexpression of LEF1, which was associated with poor differentiation, lymph node invasion and reduced overall survival [65]. Moreover, transcriptomic analysis of β-catenin target genes confirmed the activation of Wnt signaling in advanced and relapsed HNSCC tumors [66].…”
Section: Introductionmentioning
confidence: 97%
“…Alterations in the genes encoding APC have been described in the development of specific colorectal tumors [80]. The involvement of the canonical Wnt pathway in head and neck squamous cell carcinoma (HNSCC) has also been reported in several studies [81]. The Wnt/β-catenin signaling pathway interacts with many other signaling pathways, including NF-κB, Smad3, Notch, forkhead box O (FOXO) and hypoxia-inducing factor-1α (HIF-1α), extending the spectrum of biological functions of this pathway [82].…”
Section: Wnt/beta Catenin Pathwaymentioning
confidence: 95%
“…36 Recent studies have shown that the Wnt inhibitor Ipafricept can suppress the invasiveness, sphere formation and growth of CSCs in head and neck squamous cell carcinoma (HNSCC). 37 Ipafricept is being used in phase I clinical trials for treatment of cancer patients. 38…”
Section: Ipafricept (Omp-54f28)mentioning
confidence: 99%
“…134 One study showed that CAF secretory factors enhance Wnt signalling and that the Wnt inhibitor Ipafricept (OMP-54f28) suppresses proliferation of patientderived xenografts (PDXs) and inhibits CSC tumour initiation by inhibiting Wnt signalling involved in the cancer-TME interaction in head and neck squamous cell carcinoma (HNSCC). 37 Other research on breast cancer indicates that paclitaxel treatment of breast cancer cells leads to relatively high levels of ROR1 expression and that accessory cells in the TME induce activation of the Wnt5a signalling pathway by expressing ROR1, thereby promoting the stemness of breast cancer cells. Furthermore, the humanized anti-ROR1 drug cirmtuzumab inhibits activation of the ROR1 signalling pathway, which hinders the development and metastasis of breast cancer.…”
Section: Targeting the Tumour Microenvironmentmentioning
confidence: 99%